Pengaruh Penerapan Total Quality Management Terhadap Kinerja UMKM - Auliya Firyal Zahrah; Arie Apriadi Nugraha (Indonesian Accounting Literacy Journal, 2022)
This rapid development has caused business competition between MSMEs to become increasingly fierce and requires MSMEs to make maximum efforts to improve their abilities to be able to compete with other business. In order to compete, MSMEs can improve their quality by implementing a business strategy and management approach, namely TQM. This research aims to determine the effect of total quality management implementation on MSMEs performance in the Culinary Sector MSMEs in Coblong Sub-district, Bandung. Measuring the implementation of total quality management uses the characteristic dimensions of total quality management and performance measurement uses the performance dimensions of MSMEs. The type of research used is quantitative research using primary data from MSMEs and IBM SPSS v25 application. The sample used is determined using the Slovin formula with a number of 55 respondents selected using purposive sampling method. The data analysis technique used simple linear regression analysis. The results of this study indicate the effect of 63,5% of the application of total quality management on the performance of MSMEs in the Culinary Sector MSMEs in Coblong Sub-District, Bandung.